2013
DOI: 10.3390/ma6115352
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Structure and Cytotoxicity of Molecular Materials Based on Water Soluble Half-Sandwich Rh(III) and Ir(III) Tetranuclear Metalla-Cycles

Abstract: The neutral dinuclear complexes [(η5-C5Me5)2Rh2(μ-dhnq)Cl2] (1) and [(η5-C5Me5)2Ir2(μ-dhnq)Cl2] (2) (dhnqH2 = 5,8-dihydroxy-1,4-naphthoquinone) were obtained from the reaction of [(η5-C5Me5)M(μ-Cl)Cl]2 (M = Rh, Ir) with dhnqH2 in the presence of CH3COONa. Treatment of 1 or 2 in methanol with linear ditopic ligands L (L = pyrazine, 4,4′-bipyridine or 1,2-bis(4-pyridyl)ethylene), in the presence of AgCF3SO3, affords the corresponding tetranuclear metalla-rectangles [(η5-C5Me5)4M4(μ-dhnq)2(μ-L)2]4+ (L = pyrazine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The new dipyridine‐functionalized BODIPY ligand L was synthesized by the procedure described in the Supporting Information. The starting materials 1 and 2 were prepared according to reported methods . The diiodo‐BODIPY derivative was synthesized by following previously reported method .…”
Section: Methodsmentioning
confidence: 99%
“…The new dipyridine‐functionalized BODIPY ligand L was synthesized by the procedure described in the Supporting Information. The starting materials 1 and 2 were prepared according to reported methods . The diiodo‐BODIPY derivative was synthesized by following previously reported method .…”
Section: Methodsmentioning
confidence: 99%
“…However, at this stage, the parameters dictating the biological activity of these metalla-rectangles remain unclear. It has been suggested that the size and the nature of the connectors are important factors, as well as the charge and lipophilicity of the assembly [66]; however, replacing the arene ruthenium units by other half-sandwich complexes showed almost no impact on the activity [67,68]. Clearly, these studies suggest that the best combination of arenes, metals, and connectors has yet to be found.…”
Section: Water-soluble Arene Ruthenium Complexesmentioning
confidence: 96%
“…It has been proposed that this is due to the increased nuclearity and presence of the extended π‐conjugated system [10a] . Furthermore, many Ir(III) SCCs have been synthesized, with many displaying good to excellent biological properties, along with increased selectivity toward cancer cells over non‐malignant cells [6h–j,11] …”
Section: Introductionmentioning
confidence: 99%